Birth control battles: how race and class divided American religion - Wilde, Melissa J. (The University of California Press, 2020)
Social movements and American religion -- Mobilizing America's religious elite in the service of eugenics -- The early liberalizers : the church has a responsibility for the improvement of the human stock -- The supporters : God needed the white Anglo-Saxon race -- The critics : Atlanta does not believe in race suicide -- The silent groups : let the Christian get away from heredity -- The religious promoters of contraception : other people's fertility -- The forgotten half : America's reluctant endorsers of contraception.